2016
DOI: 10.1002/hbm.23278
|View full text |Cite
|
Sign up to set email alerts
|

Acute white matter changes following sport‐related concussion: A serial diffusion tensor and diffusion kurtosis tensor imaging study

Abstract: Recent neuroimaging studies have suggested that following sport-related concussion (SRC) physiological brain alterations may persist after an athlete has shown full symptom recovery. Diffusion MRI is a versatile technique to study white matter injury following SRC, yet serial follow-up studies in the very acute stages following SRC utilizing a comprehensive set of diffusion metrics are lacking. The aim of the current study was to characterize white matter changes within 24 hours of concussion in a group of hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 65 publications
8
79
0
5
Order By: Relevance
“…Increases in white matter susceptibility could be due to demyelination or increase water content (swelling). Qualitative correlation of QSM and diffusion tensor imaging results from the athlete cohort analyzed in this study 3 have shown localized agreement in white matter regions of QSM increases and decreased axial diffusion, which support to the white matter swelling hypothesis. Preliminary studies suggest that the observed gray matter decreases could be due to calcium (which is a diamagnetic [negative susceptibility] ion) influx after brain trauma 21 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Increases in white matter susceptibility could be due to demyelination or increase water content (swelling). Qualitative correlation of QSM and diffusion tensor imaging results from the athlete cohort analyzed in this study 3 have shown localized agreement in white matter regions of QSM increases and decreased axial diffusion, which support to the white matter swelling hypothesis. Preliminary studies suggest that the observed gray matter decreases could be due to calcium (which is a diamagnetic [negative susceptibility] ion) influx after brain trauma 21 .…”
Section: Discussionsupporting
confidence: 77%
“…As a non-ionizing radiative imaging modality, quantitative MRI is well-suited for use as a longitudinal scientific probe of the subtle physiological changes resulting from mTBI. Previous studies have explored mTBI-induced changes in MRI diffusion tensor imaging 2 , diffusion kurtosis imaging 3 , arterial spin labeling 4 , and functional connectivity 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used a technique called diffusion tensor imaging (DTI) to study WM changes in concussed athletes (Asken, DeKosky, Clugston, Jaffee, & Bauer, 2017; Dimou & Lagopoulos, 2014; Gardner et al, 2012). A few mTBI studies have used a more advanced DMRI technique called diffusion kurtosis tensor imaging (DKTI; Grossman et al, 2012; Grossman et al, 2013; Lancaster et al, 2016; Stokum et al, 2015), which measures deviations from the Gaussian distribution model that DTI employs. DKTI may be particularly relevant for measuring the effects of brain injury, since the complex cascade of neurochemical and neurophysiological changes that occur following brain injury may lead water molecules to diffuse in highly complex trajectories (Cervos-Navarro & Lafuente, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our group used both DTI and DKTI to investigate WM changes in both the acute (within 24 hours) and early subacute (8 days after injury) period following SRC (Lancaster et al, 2016). We found that concussed athletes demonstrated a widespread decrease in mean diffusivity (MD) and axial diffusivity (D ax ) and increase in axial kurtosis (K ax ) compared to control subjects at 24 hours post-injury.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, a systematic review of the DTI and concussion literature [65] reported on eight studies and raised concern in the literature at the time that there was so much variability in the methodology bringing together the findings of the diverse range of work and attempting to interpret the results was challenging. A more recent DTI and concussion systematic review [49] suggested that the most consistent findings were decreased mean diffusivity and/or an increase in fractional anisotropy in white matter within 6 months post-concussion [66][67][68][69][70], but these findings are not universal (i.e., the opposite patterns have also been reported in other studies) [56,62,71]. In addition, reduced radial diffusivity has been reported [68,[72][73][74], but increase and decrease in axial diffusivity have been described [68,69].…”
Section: Neuroimagingmentioning
confidence: 91%